2016
DOI: 10.3847/0067-0049/227/1/4
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Bright Stars by Optical Interferometry. I. A Search for Multiplicity Among Stars of Spectral Types F-K

Abstract: We present the first results from an ongoing survey for multiplicity among the bright stars using the Navy Precision Optical Interferometer (NPOI). We first present a summary of NPOI observations of known multiple systems, including the first detection of the companion of β Scuti with precise relative astrometry, to illustrate the instrument's detection sensitivity for binaries at magnitude differences ∆m 3 over the range of angular separation 3 -860 milliarcseconds (mas). A limiting ∆m 700 ∼ 3.5 is likely for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(23 citation statements)
references
References 99 publications
(184 reference statements)
1
22
0
Order By: Relevance
“…While some of the stars presented here do have binary companions, we could disregard the secondary star in our angular diameter fits to the primary star due to the separation between the components and/or the magnitude difference between them. Hutter et al (2016) recently demonstrated that the NPOI's detection sensitivity spans 3 to 860 mas with a magnitude difference of 3.0 (for most binary systems) to 3.5 (where the component spectral types differ by less than two). Any companions to our targets were beyond those detection limits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While some of the stars presented here do have binary companions, we could disregard the secondary star in our angular diameter fits to the primary star due to the separation between the components and/or the magnitude difference between them. Hutter et al (2016) recently demonstrated that the NPOI's detection sensitivity spans 3 to 860 mas with a magnitude difference of 3.0 (for most binary systems) to 3.5 (where the component spectral types differ by less than two). Any companions to our targets were beyond those detection limits.…”
Section: Discussionmentioning
confidence: 99%
“…We used a smoothing time of 80 minutes, since that was found to be the optimal value for angular diameter measurements as described in Hutter et al (2016).…”
Section: Selection and Characterization Of Calibrator Starsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NPOI has an unvignetted aperture of 35 cm with an effective aperture for the observations of 12.5 cm set by the diameter of the feed system optics. See Armstrong et al (1998) and Hutter et al (2016) for additional technical descriptions of this facility. Typically, observations from up to five unique baselines are obtained simultaneously; for this study, baseline lengths ranged from 18.9 to 64.4 m. A total of 291 squared visibility measurements from a 150Å wide spectral channel containing the Hα emission line (i.e., centered at 6563Å) of 48 Per were obtained at NPOI in the autumn of 2006.…”
Section: Observation Programmentioning
confidence: 99%